Tuberculous Dactylitis: An Uncommon Presentation of a Common Infection - G. Nayantara Rao; Jayasri Helen Gali; S. Narasimha Rao (Case Reports in Pediatrics)
Tuberculous dactylitis is an unusual form of osteoarticular tuberculosis involving the short tubular bones of hands and feet, which is uncommon beyond six years of age. We report the case of a fifteen-year-old adolescent boy who was diagnosed with tuberculous dactylitis, involving contralateral hand and foot. His diagnosis was delayed due to lack of suspicion of this rare entity. The report also examines the diagnostic difficulties faced by clinicians in arriving at an appropriate diagnosis.